Evaluation of tolerability and efficacy of irreversible electroporation (IRE) in treatment of Child-Pugh B (7/8) hepatocellular carcinoma (HCC). Issue 7 (July 2016) - Bhutiani, Neal; Philips, Prejesh; Scoggins, Charles R.; McMasters, Kelly M.; Potts, Melissa H.; Martin, Robert C.G.
Abstract: Introduction: Few studies have assessed the tolerability and efficacy of irreversible electroporation (IRE) in the treatment of Child-Pugh B (7/8) patients with hepatocellular carcinoma (HCC). Based on its mechanism of action, we hypothesized that IRE would be superior to microwave (MW) ablation and compared the liver tolerance and ablation success rates of these therapies in Child-Pugh B patients with HCC. Methods: 55 patients with Child-Pugh B (7/8) HCC were treated with either MW ablation (n = 25) or IRE (n = 30). Tolerance and ablation success were evaluated at 30 and 90 days and 90 days and 6 months, respectively. Tolerance was defined as stable liver function and absence of increased ascites or worsening portal hypertension. Ablation success was defined as tumor eradication on triple phase contrasted computed tomography (CT). Results: Patients undergoing IRE had shorter length of stay (p = 0.05) and 90 day readmission rate (p = 0.03) than those undergoing MW ablation. Additionally, IRE was better tolerated than MW ablation at 30 and 90 days. IRE and MW ablation resulted in 6 month success rates of 97% and 100%. Conclusion: Treatment of Child-Pugh B (7/8) HCC with IRE results in equivalent ablation success with improved liver tolerance compared with MW ablation and other ablative modalities.